A Model of Socioemotional Flexibility at Three Time Scales. (October 2013) - Hollenstein, Tom; Lichtwarck-Aschoff, Anna; Potworowski, Georges
The construct of flexibility has been a focus for research and theory for over 100 years. However, flexibility has not been consistently or adequately defined, leading to obstacles in the interpretation of past research and progress toward enhanced theory. We present a model of socioemotional flexibility—and its counterpart rigidity—at three time scales using dynamic systems modeling. At the real-time scale (micro), moment-to-moment fluctuations in affect are identified as dynamic flexibility. At the next higher meso-time scale, adaptive adjustments to changes in context are characterized as reactive flexibility. At the macro scale is flexibility that occurs across months or years, reflecting flexibility due to developmental or life transitions. Implications of the model and suggestions for future research are discussed.